Dynamic balance optimization method for aero-engine rotor without trial weight - Lingli Jiang; Changzhi Shi; Xuejun Li; Hui Ma; Yiming Cao (Advances in Mechanical Engineering)
The traditional dynamic balance methods require multiple start-stop operations for test weight adjustments, leading to high resource consumption. To improve the efficiency, accuracy, and safety of aero-engine rotor dynamic balancing, a novel dynamic balancing optimization method is proposed. A virtual prototype model of the high-speed aero-engine rotor is constructed to analyze its dynamic characteristics and derive the transfer function under unbalanced excitation. Subsequently, equilibrium equations are established to relate the unbalanced response to rotor amplitude. A multi-strategy improved sparrow search algorithm is then applied. The optimization minimizes the sum of squared residual vibrations and the maximum residual vibration at each measurement point. Experimental verification is conducted on a simulated test bench for a specific type of turbine rotor used in aerospace engines. The results demonstrate that the proposed method improves test weight efficiency and prevents local vibration overruns. It achieves an average vibration reduction of 52.56%, outperforming the 45.23% of traditional on-site dynamic balancing. This approach offers a valuable technical reference for aerospace engine vibration control.